RISK ASSESSMENT OF GROUNDWATER POLLUTION USING SENSITIVITY ANALYSIS AND A WORST-CASE SCENARIO ANALYSIS - Huysmans M.; Madarász T.; Dassargues A. (My University, 2006)
This paper illustrates how sensitivity analysis and a worst-case scenario analysis can be useful tools in risk assessment of groundwater pollution. The approach is applied to a study area in Hungary with several known groundwater pollution sources and nearby drinking water production wells. The main concern is whether the contamination sources threaten the drinking water wells of the area. A groundwater flow and transport model is set up to answer this question. Due to limited data availability, the results of this model are associated with large uncertainty. Sensitivity analysis and a worst-case scenario analysis are applied to estimate this uncertainty and build confidence in the model results.
Keywords: SENSITIVITY ANALYSIS; WORST-CASE SCENARIO ANALYSIS; GROUNDWATER POLLUTION; GROUNDWATER AND TRANSPORT MODELING